2014
DOI: 10.3389/fpsyg.2014.01093
|View full text |Cite
|
Sign up to set email alerts
|

A possible link between BDNF and mTOR in control of food intake

Abstract: Food intake is intricately regulated by glucose, amino acids, hormones, neuropeptides, and trophic factors through a neural circuit in the hypothalamus. Brain-derived neurotrophic factor (BDNF), the most prominent neurotrophic factor in the brain, regulates differentiation, maturation, and synaptic plasticity throughout life. Among its many roles, BDNF exerts an anorexigenic function in the brain. However, the intracellular signaling induced by BDNF to control food intake is not fully understood. One candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 62 publications
0
28
0
4
Order By: Relevance
“…Considerable evidence has shown that BDNF is involved in feeding and energy homeostasis via its TrkB receptor. Central infusion of BDNF suppresses appetite and reduces body weight in rodents; manipulations of the BDNF gene in animals as well as the study of BDNF gene mutations in humans have confirmed a pivotal role of the BDNF-TrkB system in feeding and weight control (Takei et al, 2014). However, while the majority of the reports have identified the hypothalamus as the main brain site responsible for the effects of BDNF on food intake, work investigating the function of the BDNF/TrkB system in the amygdala has only focused on anxiety and fear.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has shown that BDNF is involved in feeding and energy homeostasis via its TrkB receptor. Central infusion of BDNF suppresses appetite and reduces body weight in rodents; manipulations of the BDNF gene in animals as well as the study of BDNF gene mutations in humans have confirmed a pivotal role of the BDNF-TrkB system in feeding and weight control (Takei et al, 2014). However, while the majority of the reports have identified the hypothalamus as the main brain site responsible for the effects of BDNF on food intake, work investigating the function of the BDNF/TrkB system in the amygdala has only focused on anxiety and fear.…”
Section: Discussionmentioning
confidence: 99%
“…Food intake is regulated by glucose, amino acids, hormones, neuropeptides and trophic factors in the hypothalamus, and insulin is now well established as an adiposity signal acting within the brain and CNS to influence energy homeostasis through food intake and body weight [47,48]. Although it is difficult to assess the effects of insulin on the human CNS it has been suggested that insulin acts through the cerebral cortex [49] and studies have demonstrated reduced cerebrocortical response to hyperinsulinaemia in non-diabetic, obese subjects [49].…”
Section: Human Studiesmentioning
confidence: 99%
“…), widely exists in eukaryotes (Takei et al. ) and is important for food intake and dealing with environmental stresses (Abuhagr et al. ; Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…As a signal transduction pathway, the mTOR signaling pathway, which plays a vital role in nutrition regulation and has complex impact on cell growth (Cota et al 2008), widely exists in eukaryotes (Takei et al 2014) and is important for food intake and dealing with environmental stresses (Abuhagr et al 2014;Li et al 2019). The mTOR pathway is a key regulator of the balance between protein synthesis and degradation in response to nutrition quality and quantity (Wullschleger et al 2006;Wu et al 2019e), and protein synthesis is essential for cell growth, proliferation, apoptosis, and autophagy (Rohde et al 2001).…”
Section: Discussionmentioning
confidence: 99%